Hubungan Self Care Dengan Kualitas Hidup Pasien Diabetes Melitus Di Ruang Garuda Rsu Anutapura Palu: Hubungan Self Care Dengan Kualitas Hidup Pasien Diabetes Melitus Di Ruang Garuda Rsu Anutapura Palu - Hastuti Hastuti; Afrina Januarista; Nelky Suriawanto (Journal of Midwifery and Nursing, 2019)
Diabetic mellitus is the disease signed by increasing of blood sugar level and could hot be cured instantly whereas need self care. Self care is individual planning action in controlling the disease to improve the health and life quality. The aims of this research to analys the corellation between self care and life quality of diabetic mellitus patient in Garuda Ward of Anutapura General Hospital Palu. This is quantitative research it used analyses design with cross sectional approaching. Data taken by using questionniare of summary of self care (SDSCA) and diabetic quality of life (DQOL) and sample taken by total sampling technique. Population number was 30 respondents and used univariat and bivariat analyses with chi-square test. Result found that more respondents have good self care (70%) with good quality of life (73.3%) and chi-square test result that p value = 0.003 (p value< 0.05) it means statistically having corellation between self care with quality of life. Conclusion that having corellation between self care with quality of life diabetic mellitus patient in Garuda Ward of Anutapura General Hospital Palu. Patient Diabetic mellitus expeeted cold improve the self care atittude in incerasing quality of life, health state and prevent the further complication. Keywords: self care, quality of life, Diabetic mellitus